Analysis of The Islamic Education Curriculum at Tadika Al-Fikh Orchard Bukit Mertajam Pulau Pinang - Ramadhan, Harmansyah; Rahman, Abd (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
This research aims to analyze the Islamic education curriculum at Tadika Al-Fikh Orchard Bukit Mertajam Pulau Pinang in the form of structure, teaching materials, and teaching methods of the curriculum implemented. This type of research is qualitative with a descriptive approach. Data collection techniques were carried out using observation, interviews, and documentation of research objects. The data was analyzed using the Miles and Huberman model and the validity of the data using data triangulation techniques. The results of this research show that the Islamic education curriculum at Tadika Al-Fikh Orchar Bukit Mertajam prioritizes learning Islamic values, the Koran, worship, morals, and Arabic. The curriculum structure is comprehensive, providing the foundation of Islamic religion, ethics, and morals, aimed at forming a noble personality based on the Koran and Sunnah. The components include goals and vision, introduction to faith, introduction to the Koran, habituation of morals, introduction to worship, daily prayers, and knowledge of Islamic history. Teaching materials are adapted to the age development of students, arranged in the subjects of the Koran, creed, worship, morals, and Islamic history. Creative and effective teaching methods such as student-centered learning, hands-on activities, learning through play, inquiry, and contextual methods are used to make learning interesting, interactive, and relevant to children's daily lives. This research provides in-depth insight into the curriculum, structure, teaching materials, and teaching methods at Tadika Al-Fikh Orchard Bukit Mertajam, potentially improving the quality of Islamic education for preschool-age children in similar institutions.